PEMBAHARUAN DAN PERKEMBANGAN PENDIDIKAN DALAM MEMBENTUK SISWA AGAR LEBIH MAJU DI ERA DIGITAL: makna pembahruan dan perkembangan pendidikan - Vina Wulansari; Binti Maunah (LPPM Universitas Widya Dharma, 2024)
The aim of this research is to provide information regarding the development and updating of the education system. There have been several reforms in the education system in Indonesia. The National Education System has been the basis for implementing the Indonesian education system since 2003 until now. The education system has undergone several reforms to move closer to this goal. However, the problems and challenges associated with efforts to make the education system more competitive compared to other countries require more attention from the government and decision makers in parliament. This article begins by discussing the factors that influence educational change and reform. Another goal is educational reform. Third, issues such as the dynamics of life. Considering that producing and developing quality human resources is very important for Indonesian education, educational reform needs to be implemented deeply Keywords: Technology, Learning, digital